Organizing for Life - Davis, Creston (Identities: Journal for Politics, Gender and Culture, 2015)
In this article, I identify the need for intellectuals to organize around the core building blocks of life, air, water, and food. The article examines the lack of such organization on the left and the need to overcome the differences that fragment us. The article then goes on to propose a way of organizing in dialectical terms between protests, revolts on the one hand, and a “base” organized around a school committed to difference, discourse and conversation, and above all democracy. Author(s): Creston Davis Title (English): Organizing for Life Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 61-66 Page Count: 6 Citation (English): Creston Davis, “Organizing for Life,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 61-66.